Phlomis fruticosa l. exerts in vitro antineurodegenerative and antioxidant activities and induces prooxidant effect in glioblastoma cell line - Stojković, Dejan (2022)
Despite the significant advances in drug development we are witnessing the inability of health systems to combat both neurodegenerative diseases and cancers, especially glioblastoma. Hence, natural products are comprehen-sively studied in order to provide novel therapeutic options. This study aimed to explore anti-neurodegenerative and anti-glioblastoma potential of extract of Phlomis fruticosa L. using in vitro model systems. It was found that the methanol extract of P. fruticosa was able to efficiently reduce activities of enzymes linked to neurodegenera-tive disease including acetylcholinesterase, butyrylcholinesterase and tyrosinase. Furthermore, P. fruticosa ex-tract has shown excellent antioxidant potential, as evidenced by six different methods. Analysis of cytotoxic ef-fect of P. fruticosa extract on A172 glioblastoma cell line revealed that the concentration of the extract necessary for 50 % inhibition of A172 growth (IC50) was 710 μg/mL. The extract did not induce changes in proliferation and morphology of A172 glioblastoma cells. On the other side, production of ROS was increased in A172 cells treated with the extract. Observed cytotoxic effect of P. fruticosa extract might be based on increase in ROS generation upon treatment. Quantitative chemical analysis revealed the presence of twelve different polyphenols with the cis 3-O-caffeoylquinic acid being the most abundant. This study provided scientific evidence for further exploration of P. fruticosa as a promising natural anti-neurodegenerative therapeutic option.